2021
DOI: 10.1088/1755-1315/648/1/012114
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution assessment in paddy fields and dryland in Bandung District, West Java

Abstract: Excessive use of fertilizers and pesticides causes the accumulation of heavy metals in intensive agricultural land. Besides, the development of industries around the agricultural area further aggravates the accumulation of heavy metals. This study aimed to assess spatial distribution of heavy metal contamination in agricultural land in Bandung District. In this study, seven concentrations of heavy metals (Cr, Pb, Cd, Co, Cu, Ni, and Zn) in soils were analysed from 273 sampling sites in paddy and horticultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Fertilizers and pesticides might continuously increase heavy metal ecological risks [31]. It has been demonstrated that higher Cd and Zn ecological risk on drylands could arise from continuous agriculture [32]. Additionally, the Cu concentration determined in the study area exceeded the local background values and the results of the impact of distances on the potential ecological risk index of heavy metals showed that it was related to other lands, such as woodlands, orchards, tea plantations, and grasslands.…”
Section: Potential Sources Of the Heavy Metals Ecological Risksmentioning
confidence: 79%
“…Fertilizers and pesticides might continuously increase heavy metal ecological risks [31]. It has been demonstrated that higher Cd and Zn ecological risk on drylands could arise from continuous agriculture [32]. Additionally, the Cu concentration determined in the study area exceeded the local background values and the results of the impact of distances on the potential ecological risk index of heavy metals showed that it was related to other lands, such as woodlands, orchards, tea plantations, and grasslands.…”
Section: Potential Sources Of the Heavy Metals Ecological Risksmentioning
confidence: 79%
“…Furthermore, approximately 46% of irrigation systems in Indonesia have deteriorated due to aging infrastructure [177]. Urban and industrial developments near paddy field areas also pose a threat of hazardous chemical contamination [177,178]. Climate change can cause changes in rainfall patterns, including a higher frequency of extreme rainfall, and could further negatively affect water availability and agricultural infrastructure [179], especially in rain-fed areas.…”
Section: Water Conservationmentioning
confidence: 99%